2005
DOI: 10.1073/pnas.0500661102
|View full text |Cite
|
Sign up to set email alerts
|

Multiple subsets of side-chain packing in partially folded states of α-lactalbumins

Abstract: Photochemically induced dynamic nuclear polarization NMR pulselabeling techniques have been used to obtain detailed information about side-chain surface accessibilities in the partially folded (molten globule) states of bovine and human ␣-lactalbumin prepared under a variety of well defined conditions. Pulse labeling involves generating nuclear polarization in the partially folded state, rapidly refolding the protein within the NMR sample tube, then detecting the polarization in the well dispersed native-state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 57 publications
2
45
0
Order By: Relevance
“…Population of this molten globule state leads to NMR line broadening, which indicates that the component species have trapping times on the millisecond timescale (46). Indeed, the NMR line broadening (47) and complex interconversion behavior over a wide range of timescales (48) that are typical features of molten globule states are readily accounted for by subdiffusional behavior on a rugged energy landscape, as proposed here.…”
Section: Discussionmentioning
confidence: 83%
“…Population of this molten globule state leads to NMR line broadening, which indicates that the component species have trapping times on the millisecond timescale (46). Indeed, the NMR line broadening (47) and complex interconversion behavior over a wide range of timescales (48) that are typical features of molten globule states are readily accounted for by subdiffusional behavior on a rugged energy landscape, as proposed here.…”
Section: Discussionmentioning
confidence: 83%
“…Molten globules are believed to have dynamic hydrophobic cores due to the lack of signal in the near-UV CD spectrum and the broadening of NMR signals of aromatic groups (6,7). Recent studies have shown that the side chains in the α-lactalbumin molten globule exchange between several well defined conformations, representing a dynamic ensemble of states with specific tertiary interactions (9).…”
Section: Creb Binding Protein | Folding Upon Binding | Nmr Spectroscopymentioning
confidence: 99%
“…Under destabilizing conditions such as low pH, addition of cosolvents, high temperature, or combinations thereof, apo-␣-lactalbumin exists in an MG state. The MG state is characterized by the absence of long-lived tertiary structure, but it still contains a high degree of secondary structure (20,21), with a radius of gyration only Ϸ10% larger than the native state (22,23). The MG state of ␣-lactalbumin has recently attracted considerable interest when it was realized that it may act as an important component causing apoptosis of tumor cells (24).…”
Section: Conformational Transition Kinetics Of ␣-Lactalbumin From An mentioning
confidence: 99%